Abordagem Ciência, Tecnologia e Sociedade em uma disciplina do curso deespecialização em ensino de ciências por investigação - Santer Alvares de Matos (2014)
Empirical studies have reinforced the importance of the inclusion of discussions that enable reflections on teaching approach in Science, Technology and Society (STS) in teacher education. These studies also indicate that reflections STS still occupy incipient space in the teacher training process. Counterpoint to this perspective, the Graduation Course in Inquiry-based Science Education (ENCI), offered by the Center for Science and Mathematics Teaching, has the subject "Science Teaching Approach in Science, Technology and Society I," with the goal of "discuss a curriculum-driven approach regarding Science, Technology and Society". The present research investigated the approaches of Science, Technology and Society currently in the subject STS I, contributing to the scope of research in the area. The subject STS I occurs in a Virtual Learning Environment, which was used as a production database. From a theoretical-methodological perspective this research was sustained in the sociology of scientific knowledge and analytical methodology of discursive dynamics. The sociology of scientific knowledge allowed the analysis approach of Science, Technology and Society and the expanding use of an analytical matrix for STS approach proposed in another research context. The analytical methodologies discursive dynamics and social networking enabled qualification analysis of discursive interactions on the discussion that occurred in the subject. The matrix used allowed us to understand the approaches present in the STS tasks of subject STS I. The matrix also allowed the analysis of the STS approach in a different context from which it was created, expanding its analytical context. In the discussion forum, the action of the tutor showed up and marked by centralization of authority discourse. The final considerations for research contributions on the subject STS I and the research field of Sciences Education were presented, and exhibit potential issues for future research.